Numerical solutions to some inverse problems - Van, Cong Tuan Son (Kansas State University, 2017)
In this dissertation, the author presents two independent researches on inverse problems: (1) creating materials in which heat propagates a long a line and (2) 3D inverse scattering problem with non-over-determined data. The theories of these methods were developed by Professor Alexander Ramm and are presented in Chapters 1 and 3. The algorithms and numerical results are taken from the papers of Professor Alexander Ramm and the author and are presented in Chapters 2 and 4.
Keywords: Heat transfer; Inverse problems; Scattering theory; Non-over-determined scattering data